РАСПРЕДЕЛЕНИЕ МОЛОДИ ПРОМЫСЛОВЫХ И СОРНЫХ РЫБ МЕЛКОВОДИЙ КАПШАГАЙСКОГО ВОДОХРАНИЛИЩА И РЕКИ ИЛИ (Experimental biology, 2009)
The material was going in a coastal zone Kapshagai of reservoir and from of river Ili. Or from middle of July prior to the beginning August of the current year. In 2009 Rhinogobius similis. In the 2009 year concentration, the number and species structure young fish of fishes was higher, than last in 2008.
Keywords: concentration; coastal